A mulher que logo sou estilo, escritura e otobiografia - Campos, Aline de Souza (2016)
This work proposes a listening to the feminine's styles of the Psychology and Pedagogy students at the Federal University of Mato Grosso, Cuiabá. In a movement of experimentation, I heard the echoes of my life-experiences while psychologist-woman-researcher on the written production of those students. To mobilize that listening, I used the Workshop of Transcreation, designed and operationalized as a concept and practice of research by the project Writreadings: a way of reading-writing amidst life. Through the Workshop of Transcreation Vita Femina, I used texts by Virginia Woolf and Florbela Espanca investing in a new typology: a Otobiografemática Workshop. The listening of that written production took place through the otobiographic research, developed by Monteiro from the Nietzschean concept of life- experiences and the otobiographie concept, proposed by Derrida. From this movement raise the possibilities of composition, experimentation and variations of individual styles.